Linear Optical properties of Pheomelanine pigment extraction from red wool - Obeid, Mohammed T.; Hussain, Waleed A.; Radhi, Wisam A.; Jabir, Abduljabar A.; Alammam, Dhiaa A. Abd- (Sulaimani Journal for Pure and Applied Sciences, 2015)
The aims of this research are the extract of Pheomelanine pigment from red wool and prepared of it as a thin film by repeat-spray method. We study the optical properties of the Pheomelanine thin film such as the absorbance (A), Transmittance (T), absorption coefficient (α), refractive index (n) and extinction coefficient (k). We calculate the energy gap ( Eg), Urbach tail (Eu), oscillator energy (Eᵒ), dispersion energy (Ed), static refractive index (nᵒ), static dielectric constant (εᵒ) and spectra moments ( M-1 and M-3).
Keywords: Pheomelanine thin filmRepeatspray methodOptical properties